Antibiotics impair immune checkpoint inhibitor effectiveness in hispanic patients with non-small cell lung cancer (AB-CLICaP) (2020)
Background The intestinal microbiota is an important factor in modulating immune‐mediated tumor cell destruction. Alterations in the microbiome composition have been linked to reduced efficacy of immune checkpoint inhibitor (ICI) therapies. Therefore, antibiotic treatment (ATB), which modifies the diversity of the gut bacteria populations, could lead to a reduced efficacy of ICI treatments. Methods This was a retrospective cohort study. Patients with advanced non‐small cell lung cancer (NSCLC) treated with anti‐programmed cell death ligand‐1 (PD‐L1) alone, or in combination in three different countries in Latin America were included. After identification, patients were placed into three groups: Non‐ATB exposed (no‐ATB), exposed within 30 days of the first dose of ICI (pre‐ICI ATB) and patients receiving ATB concomitantly with ICI (ICI‐ATB). Progression‐free survival (PFS), overall survival (OS) and response rates to treatment with ICI were assessed. Results A total of 140 patients were included, of which 32 patients (23%) received ATB treatment. The most common ATB types were fluoroquinolones and B‐lactams. No differences in survival according to antibiotic type were identified. Median OS in patients not exposed to ATB was 40.6 months (95% CI: 32–67.7), compared with 20.3 months (95% CI: 12.1‐non‐reached [NR]) for patients with pre‐ICI ATB treatment and 24.7 months (95% CI: 13‐NR) for patients treated with ATB concomitantly with ICI. There were no significant differences in terms of PFS, or response rates across all treatment groups. Conclusions Antibiotic treatment was associated with reduced OS in Hispanic patients with NSCLC treated with ICIs.